Cultural Dimensions, Ethical Sensitivity, and Corporate Governance - Chan, Alex Wing-ho (Journal of business ethics, 2012)
The economic globalization process has integrated different competitive markets and pushes firms in different countries to improve their managerial and operational efficiencies. Given the recent empirical evidence for the benefits to firms and stakeholders of good corporate governance (CG) practice, it is expected that good CG practice would be a common strategy for firms in different countries to meet the increasingly intense competition; however, this is not the case. This study examines the differences in CG practices in firms across different countries using the concept of ethical sensitivity. Through the regression analysis of 271 firms in 12 countries and regions, it is found that Hofstede’s cultural dimensions can explain the differences in CG practices. Furthermore, the results demonstrate the influence of culture on ethical sensitivity, which eventually determines the CG practices in different regions.